Corregulação da publicidade infantil : uma possível solução para os conflitos entre livre iniciativa, liberdade de expressão comercial e proteção integral da criança - Flores, Márcia Lunardi (2018)
This study aims to analyze the extent to which the Brazilian constitutional order allows the State to limit the freedom of commercial expression and free initiative in favor of the principle of the integral protection of the child. To this end, the relationship between children, consumption and advertising, within the context of a capitalist and hypermodern society, is verified. A possible form of regulation of children's advertising should therefore be considered, in light of the theory of the linking of individuals to fundamental rights as a means of guaranteeing the full protection of the child and the preservation of the right to freedom of commercial expression and free enterprise. The investigation of some regulatory models in force in the international scenario, such as the Quebec, Spain, United Kingdom, United States, France and Italy systems, was necessary to search for parameters suitable for harmonization between the interests of free enterprise and freedom of expression with the need to protect children. The starting point was the Quebec system because it is a more restrictive model for children's advertising. European elected models, on the other hand, present a greater dialogue between self-regulation, state legislation and civil society. The US system has a greater emphasis on self-regulation, but there is room for State action through regulatory agencies. The comparison of international models with the Brazilian system of self-regulation of advertising has shown that the Brazilian model lacks a greater dialogue with the State, as well as more efficient ways of protecting the child in relation to exposure to advertisements. The Brazilian constitutional order, while at the same time consecrating free initiative and free expression, adopted as a paradigm the integral protection of children, giving priority to their interests. It is possible, therefore, to have a greater state action in defense of the child's interests in relation to advertising. In order to equalize the advertising market and its right of free initiative and expression and child protection, co-regulation is a viable alternative, imposing limits that obey the criteria of reasonableness and proportionality.